PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PEMANTAUAN GARAM BERYODIUM DI DINAS KESEHATAN KABUPATEN SLEMAN = MANAGEMENT INFORMATION SYSTEM DEVELOPMENT FOR IODINED SALT MONITORING AT THE DISTRICT HEALTH OFFICE SLEMAN ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: The research was conducted to develop an information system for iodined salt monitoring to support the plan of increasing the iodined salt consumption at the District Health Office, Sleman Regency. This descriptive and qualitative research was carried out by implementing in-depth interview to subjects who were involvetitin the activity of the monitoring. Observation was also performed to two objects, namely the structure and the procedure of information. Method: The collected data were analyzed descriptively by applying scaled means analysis and qualitatively by conducting a content analysis. The system development was designed by using the approach of Framework for the Application of System Techniques (FAST). Results: The observation to the problem, its scope and property as well as the interview with the subjects indicate that the research subjects at all levels from top managers to persons in the transactional level as well as those who are at cross section department support the development of monitoring system to the consumption of iodined salt, and this system is reliable to perform. The evaluation toward the work of the information system on its completeness, accessibility, accurateness, ease as well as representatively shows that the value of scaled means analysis increases from 2,48 to 4,80, the former figure is before and the latter is after the development of the system. Conclusion: It is concluded that the value of the scaled means analysis from each indicator of the monitoring system assessment increases before the development of the system. The results of the content analysis demonstrate the benefits of the new system in supporting the monitoring â¢ activity toward the consumption of iodines salt and it also supports the plan. All of the subjects claim a positive response to the new system. Suggestions based on the conclusion might go to the government health institution to socialize the new system and to make a policy to maintain such a system from the process of data collection to the decision making, so that the system can go well. Moreover, a network model should be developed in that the data and information can be accessed by online. Keywords: information system, monitoring, iodined salts